ONTOGuide: A Domain Ontology for the Retrieval and Publication of Online Educational Resources - Otero-Cano, Paola-Andrea; Sierra-Martínez, Luz-Marina; Ordoñez-Eraso, Hugo-Armando (Universidad Pedagógica y Tecnológica de Colombia, 2023)
In today's digital landscape, the exponential growth of information on the web has led to challenges in its organization and management. Often, resources published on the web lack proper structure or appropriate descriptions, thus making it difficult to establish connections with similar resources—a critical issue when searching for educational materials. In such searches, the need for clear, reliable, and immediately available information takes precedence. There are strategies to tackle this problem, the use of ontologies stands out as a compelling solution because they offer a well-defined, lucid, and precise structure within specific domains. Consequently, this study focuses on crafting a domain-specific ontology that furnishes the required knowledge for publishing and retrieving educational resources from the web. We follow the methodology outlined in "Ontology Development 101: A Guide to Creating Your First Ontology" to design it. The outcome is a domain ontology applicable from two distinct perspectives: an academic standpoint, catering to those who seek to understand the underlying concepts, properties, and relationships involved in resource publication and retrieval; and an industrial one, serving as a support tool for companies or institutions aiming to navigate the process of publishing and retrieving resources to improve the management of their knowledge bases.